PEMBELAJARAN MENULIS CERITA PENDEK DENGAN MENGGUNAKAN METODE THINK TALK WRITE - Dwi Citra Ayu Puspita Sari; Annisa Nurhanifah; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
Short story writing is one of the skills that must be mastered by students especially class XI. Apparently, writing has not become a cultural activity so the role of teachers is very important in improving it. This study aims to (1) to find out the activities of teachers and students in short story learning using Think Talk Write method (2) to see the significant difference after being given treatment with Think Talk Write method. The method used in this research is an experimental method. Samples used are students of class XI SMK BIB Ngamprah. (1) seen from the activity of teacher and student that can be done 86 and 87,5 which mean very good (2) result of research indicate that result of calculation of Mann-with test 0.000, hence significance value ≤ 0,05 can be concluded that there a significant influence.